"The Trouble with Women" - Vilches, Gerardo (Filanderas, 2017)
The Trouble with Women (Anagrama, 2017) is the latest work by Jacky Fleming (London, 1955). This British author, little known in Spain, has been publishing decades of graphic humor cartoons in media such as The Independent or The Guardian. In this small book, a brief satirical essay, he applies his acid gaze on the history of the last centuries, from a perspective that could be considered close to the herstory, but that, above all, seeks to highlight the absurdity of an entire series of sexist expositions covered with a patina of scientism.
Keywords: Comic; Jacky Fleming; Feminism; Women's HIstory; Graphic Humour